Almanca Tuhfe/Deutsches Geschenk (1916), or: How does one write German with Arabic letters - DOĞAN AVERBEK, GÜLER (My University, 2022)
© 2022, European Association for Lexicography. All rights reserved.Versified dictionaries are bilingual/multilingual glossaries written in verse form to teach essential words in any foreign language. In Islamic culture, versified dictionaries were produced to teach the Arabic language to the young generations of Muslim communities not native in Arabic. In the course of time, many bilingual/multilingual versified dictionaries were written in different languages throughout the Islamic world. The focus of this study is on the Turkish-German versified dictionary titled Almanca Tuhfe / Deutsches Geschenk [German Gift], published by Dr. Sherefeddin Pasha in Istanbul in 1916. This dictionary is the only dictionary in verse ever written combining these two languages. Moreover the dictionary is one of the few texts containing German words written in Arabic letters (applying Ottoman spelling conventions). The study concentrates on the way German words are spelled and tries to find out, whether Sherefeddin Pasha applied something like fixed rules to write the German lexemes.
Keywords: Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; DİL VE DİLBİLİM; Arts & Humanities (AHCI); ARTS & HUMANITIES; LANGUAGE & LINGUISTICS; Dil ve Dilbilim; Sosyal Bilimler ve Beşeri Bilimler; Dilbilim ve Dil; Language and Linguistics; Social Sciences & Humanities; Linguistics and Language; Ajamiado-Literatur; arabische Schrift; Osmanisch-deutsche Wörterbücher; osmanisch-türkische Orthographie; Osmanische Wörterbücher; Wörterbücher in Versen; Ajamiado-Literatur; arabische Schrift; Osmanisch-deutsche Wörterbücher; osmanisch-türkische Orthographie; Osmanische Wörterbücher; Wörterbücher in Versen